Religion, customs and local identity: bi-spirituality in rural Ukraine. Issue 2 (3rd April 2018) - Kaneff, Deema
ABSTRACT: Identity is a complicated matter in the religiously diverse Ukraine. Based on long-term anthropological fieldwork carried out in a village in Odessa province, I explore the association between spirituality and identity. The focus is on the relationship between institutionalised religion (namely the Orthodox Church and the priest as its representative) and local customs (attributed to the Bulgarian heritage of the population). The distinction between 'customs' and 'religion' – an emic one to which both villagers and their priest subscribe – divides their spiritual loyalties and often creates tensions in the community. Such tensions, I suggest, are not a threat to community integrity as much as a means by which collective identity is managed. Bi-spirituality provides a means of belonging, contributing to the community's ethnic minority status in an emerging Ukrainian nation-state.